Grounds for termination of franchise agreement in Jordan - Khasawneh, Mohammad Saud; Yaacob, Nurli; Abdul Rahman, Rohana (IISTE, 2016)
Purpose: This study explores the termination of franchise agreement in Jordan. The study discusses the grounds to terminate the franchise agreement by each party whether franchiser or franchisee. Regulating the franchise sector by a specific act minimizes unfair termination and helps strengthen the franchise sector in Jordan. Design/methodology/approach: This study is qualitative. Eleven in-depth semi-structured interviews were conducted with the relevant parties involved in franchise agreements as well as legislatures. The analysis was thematically conducted and accordingly supported by sufficient excerpts.Findings: The study found several grounds to terminate the franchise agreement by the parties involved. Emphatically, the participants were unanimous regarding the breach of the contract terms and conditions as the main ground to terminate the franchise agreement.Research limitations: The research participants were franchisors, franchisees and parliamentarians in Jordan. Additionally, the data collection constrained by funds paucity and difficulties in securing appointments with the participants who were always busy and not available. Two of the participant answered the interview questions by filling up the questions instead of face to face and recorded interview.Practical implications: The study suggests that the termination grounds of the franchise agreement need to be more specific and limited to certain provisions which should be provided by specific act for this purpose. Otherwise the unfair termination whether by the franchisers or franchisees will continue. Originality/value: Even though franchise agreement literature s are aplenty, this study, however, is the first attempt at qualitatively exploring in-depth regarding the termination grounds for the franchise agreement in Jordan.Paper type: Research Paper